2019
DOI: 10.3390/antiox8090342
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory, Anti-Arthritic and Anti-Nociceptive Activities of Nigella sativa Oil in a Rat Model of Arthritis

Abstract: This study investigated the preventive efficacy of the crude oil extracted from Nigella sativa seeds in a rat model of arthritis induced by using complete Freund’s adjuvant (CFA). Nigella sativa oil at 1.82 mL/kg or 0.91 mL/kg (corresponding to 1596 and 798 mg/kg, respectively) was orally administered for 25 days from the day of immunization. One immunized group was treated orally with indomethacin (3 mg/kg) as a reference drug. Body weight growth rate, paw swelling, arthritis score, mechanical allodynia, loco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 39 publications
2
55
0
Order By: Relevance
“…EVO and NS oils have previously been evaluated for their chemical composition and antioxidants properties [30,47] and significant differences have been identified; total antioxidant activity, DPPH radical-scavenging activity, superoxide scavenging activity and catalase-like activity were +77%, +62%, +90%, +98% and +91% higher in EVOO than in NS oil [30]. The higher antioxidant properties of EVOO can be explained by the much higher concentration of the most active tocopherol (α-tocopherol), found in EVOO at 284 mg kg −1 and in NS oil at 27 mg kg −1 [31,47] and to the presence many other strong antioxidants in EVOO such as tyrosol, hydroxytyrosol and secoiridoid derivatives found in relatively high concentration and absent in NS oil. In particular, tyrosol, hydroxytyrosol and the main secoiridoid derivatives (the dialdehydic form of decarboxymethyl elenolic acid linked to hydroxytyrosol or to tyrosol, an isomer of the oleuropein aglycon, and ligstroside aglycon), were found in the EVOO under investigation at concentrations of 6.7, 9.8 and 583.6 mg kg −1 , respectively [30,47].…”
Section: Discussionmentioning
confidence: 92%
“…EVO and NS oils have previously been evaluated for their chemical composition and antioxidants properties [30,47] and significant differences have been identified; total antioxidant activity, DPPH radical-scavenging activity, superoxide scavenging activity and catalase-like activity were +77%, +62%, +90%, +98% and +91% higher in EVOO than in NS oil [30]. The higher antioxidant properties of EVOO can be explained by the much higher concentration of the most active tocopherol (α-tocopherol), found in EVOO at 284 mg kg −1 and in NS oil at 27 mg kg −1 [31,47] and to the presence many other strong antioxidants in EVOO such as tyrosol, hydroxytyrosol and secoiridoid derivatives found in relatively high concentration and absent in NS oil. In particular, tyrosol, hydroxytyrosol and the main secoiridoid derivatives (the dialdehydic form of decarboxymethyl elenolic acid linked to hydroxytyrosol or to tyrosol, an isomer of the oleuropein aglycon, and ligstroside aglycon), were found in the EVOO under investigation at concentrations of 6.7, 9.8 and 583.6 mg kg −1 , respectively [30,47].…”
Section: Discussionmentioning
confidence: 92%
“…They observed an anti-inflammatory effect of NSO in a higher dose, but not in low one in a model of FA-induced arthritis after 25 days of treatment. The effect was less intense than that of indomethacin [ 34 ]. These observations might confirm that NS has an anti-inflammatory effect that is less potent than NSAIDs, and in a chronic model of arthritis, a longer duration of administration is required to validate it.…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent results were also reported in previously published research. Nasuti et al noticed that NSO had antinociceptive properties in a contralateral hind paw but not in a inoculated one after 25 days of treatment [ 34 ]. This observation differs from the present study, which did not report the antinociceptive effect in the contralateral paw, but the final evaluation was performed after a shorter duration of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no considerable change occurred in % of inhibition of arthritis, spontaneous locomotor activity, plasma levels of IL-6, CRP, and albumin compared to the arthritic control group. Additionally, no significant antinociceptive activity was reported in the inoculated hind paw compared to the arthritic control group [65]. Another study in Freundʼs Complete Adjuvant-induced arthritic rats also indicated that TQ (2.5 and 5 mg/kg BW) led to a significant reduction in clinical arthritis, radiological scores, and serum TNF-α and IL-1β levels in comparison with the control group [50].…”
Section: Animal Studiesmentioning
confidence: 97%
“…Arjumand et al [48] reported that 10 mg/kg BW TQ caused a considerable reduction in the arthritic score and CRP levels, significant normalization of total leukocyte count (TLC), lymphocytes, neutrophils, and monocytes; significant alleviation of inflammation, pannus formation, and bone erosion; and a significant decrease in mRNA expression levels of toll-like receptor (TLR)2, TLR4, IL-1, nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), and TNF-α in rats with Freundʼs Complete Adjuvant-induced arthritic compared to the arthritic control group, while there was no significant change in RF compared to the arthritic control group. Nasuti et al [65] noted that N. sativa oil administration (1596 and 798 mg/kg BW for 25 days) contributed to significant alleviation in paw volume and had significant antinociceptive activity in contralateral hind paw in Freundʼs Complete Adjuvant-induced arthritic rats compared to the arthritic control group; however, reduction in paw volume and the arthritis score was not significant compared to the arthritic control group. Moreover, no considerable change occurred in % of inhibition of arthritis, spontaneous locomotor activity, plasma levels of IL-6, CRP, and albumin compared to the arthritic control group.…”
Section: Animal Studiesmentioning
confidence: 99%